A Case Series of Spontaneous Chylothorax in Lymphoma - Widiastuti Widiastuti; Eri Rakhmawati; Yusuf Syaeful Nawawi; Ana Rima (Indonesian Journal of Cancer, 2021)
Introduction: Chylothorax is a rare condition originating from lymphatic system damage as an accumulation of chyle in the pleural space. It can be classified into spontaneous or non-traumatic, traumatic, and idiopathic. A spontaneous chylothorax is primarily caused by neoplasm, such as lymphoma.Case Presentation: Herein, we report two cases of chylothorax presenting as massive pleural effusion in two patients of a 23-year-old male with nodular sclerosis type Hodgkin’s lymphoma and a 31-year-old female with metastatic lymphadenopathy of undifferentiated carcinoma from non-Hodgkin’s lymphoma.Conclusion: A spontaneous chylothorax is a rare condition that may lead to a life-threatening event when it is not properly and promptly treated.